A multivariate model for predicting PPGP considering postural adjustment parameters. (August 2020) - Aldabe, Daniela; Milosavljevic, Stephan; Bussey, Melanie D.
Abstract : Background: Prospective studies have described evidence about the risk of developing pregnancy-related pelvic girdle pain (PPGP) such as, parity, previous history of low back and pelvic girdle pain. No previous studies have prospectively associated PPGP with postural control. Aim: This study aimed to identify postural control predictors of PPGP during pregnancy. Methods: Forty-six pregnant women were surveyed throughout their pregnancy for the presence of PPGP. At baseline, participants were evaluated for muscle latencies, mediolateral centre-of-pressure (COP) displacement and velocity during single-leg lift performed with eyes open and closed. PPGP was considered if they presented with one positive clinical assessment as well as pain within the pelvic area. Results: Eighteen (45%) of the participants developed PPGP. This group presented with PPGP around a mean 29th week (SD = 5.7), with mean pelvic pain intensity of 4 mm VAS (SD = 2) on a (0–10 cm VAS) and mean PPGP questionnaire score of 21.5 points (SD = 10.6) out of a possible 100 points with 0 indicating no functional disability. The two factors that were significantly associated with PPGP were the right and left biceps femoris (BF) muscle. For every 50 ms of difference of BF muscles latency between eyes open and closed, the risk of PPGP increases by 20% (right BF) and 30% (left BF) to develop PPGP. Conclusion(s): This study shows that BF muscle delay during single-leg lift presented at baseline was a significant predictor for the development of PPGP in late pregnancy. Highlights: Forty-five percent of the pregnant cohort presented with pelvic girdle pain in late pregnancy. The prediction model for PPGP was built considering postural control parameters as well as known risk factors. Bicep femoris muscle delay during single leg lift was a significant predictor for the development of PPGP in late pregnancy. Pregnant women who have increased reliance on the visual system for postural control may be at increased risk for PPGP.